PENERAPAN ABC DALAM SISTEM HARGA TRANSFER - Widiatmoko, J. (Gema Stikubank, 2000)
The trend toward desentralization and the implementation of the profit center concept in the 1960s and 1970s provided increased autonomy at the divisional level or subsidiary of many corporations. at the same time , it created the need for a sound transfer pricing system to assure the optimal allocation of corporate resource and to provide meaningful measure of divisional profit performance.The need for an effective transfer pricing system remains strong, althought the transfer pricing problem of domestic or multinational companies are complex enough.Â These are many transfer pricing systems can be used by companies. They have weaknesses, one of them is the dificulty to achive goal congruence. This artcle discuses how a company solves its transfer pricing problems by using Activity Based Costing.